Managing childhood allergies and immunodeficiencies during respiratory virus epidemics - The 2020 COVID-19 pandemic: A statement from the EAACI-section on pediatrics - Brough, Helen A; Kalayci, Omer; Sediva, Anna; Untersmayr, Eva; Munblit, Daniel; Rodriguez Del Rio, Pablo; Vazquez-Ortiz, Marta; Arasi, Stefania; Alvaro-Lozano, Montserrat; Tsabouri, Sophia; Galli, Elena; Beken, Burcin; et al. (Pediatric allergy and immunology, 2020)
While the world is facing an unprecedented pandemic with COVID-19, patients with chronic diseases need special attention and if warranted adaptation of their regular treatment plan. In children, allergy and asthma are among the most prevalent non-communicable chronic diseases, and healthcare providers taking care of these patients need guidance. At the current stage of knowledge, children have less severe symptoms of COVID-19, and severe asthma and immunodeficiency are classified as risk factors. In addition, there is no evidence that currently available asthma and allergy treatments, including antihistamines, corticosteroids, and bronchodilators, increase the risk of severe disease from COVID-19. Most countries affected by COVID-19 have opted for nationwide confinement, which means that communication with the primary clinician is often performed by telemedicine. Optimal disease control of allergic, asthmatic, and immunodeficient children should be sought according to usual treatment guidelines. This statement of the EAACI Section on Pediatrics puts forward six recommendations for the management of childhood allergies and immunodeficiencies based on six underlying facts and existing evidence.
Keywords: Pneumonia, Viral; pandemie; pediatrie; Infant; Humans; corticosteroids; coronavirus; kojenec; koronavirové infekce; dítě; alergie; Child; Academies and Institutes; Pandemics; Coronavirus Infections; children; Hypersensitivity; lidé; Europe; asthma; treatment; biologics; akademie a ústavy; předškolní dítě; COVID-19; Pediatrics; Practice Guidelines as Topic; Betacoronavirus; Adolescent; immunodeficiency; směrnice pro lékařskou praxi jako téma; allergy; syndromy imunologické nedostatečnosti; SARS-CoV-2; Child, Preschool; Evropa; virová pneumonie; mladiství; Immunologic Deficiency Syndromes